Using of Out Budget Financial Resources in University Libraries and Proposal for an Alternative Financing Model in Turkey - Mesut Kurulgan; Fatih Temizel (Türk Kütüphaneciliği)
Like other organizations, university libraries have a lot of opportunities in today's rapidly developing world. Reaching a very high speed in information production necessitates important development in its storing and retrieval to present it to users. Advancement of technology has not only provided new opportunities but has also generated new demand in these fields. However, technological developments and rapidly rising information requirements of library users requires much more financial resources. State funds, seen as the traditional financial resources, have reached their natural borders. University libraries that have to develop themselves and need to offer high quality services to their users, have to develop innovations in order to reach these objectives. Towards this end, published material on the practices in developed and developing nations have been analyzed. Thus, by determining the Turkey's position in internationalpractices, we offer alternative proposals. It is seen that the most important contribution would be through donations. It is also observed that donated funds have been used effectively in the United States. For realizing this, it is necessary that the universities should hire experts for gathering out of budget financial resources. This will be a breakthrough for development of university libraries in Turkey.